PENGARUH RASIO KEUANGAN EARLY WARNING SISTEM DAN PROFITABILITAS TERHADAP SOLVABILITAS PERUSAHAAN ASURANSI UMUM SYARIAH PERIODE 2017-2021 - Rustam, Rustamunadi; Siti Nur Kholifah (Syar'Insurance: Jurnal Asuransi Syariah, 2023)
This research aims to determine the effect of liquidity ratios, own retention ratios, expense ratios, and company size on the company's solvency level as proxied by the Risk Based Capital (RBC) ratio. The sample for this research is a sharia life insurance company that publishes financial reports for the 2017-2021 period. This type of research is quantitative research. The data collection technique used in this research is documentation. The data used is secondary data, namely in the form of financial reports and performance summaries published on the official website of the company related to this research.